Stigma Masyarakat Melayu terhadap Orang Dengan Gangguan Jiwa - atika ulfa safitri; Fathra Annis Nauli; Jumaini Jumaini (STIKes Payung Negeri Pekanbaru, 2022)
abstract Introduction: Stigma in society is one of the inhibiting factors in healing people with mental disorders, this is due to the socio-cultural nature of Indonesian society such as the Riau Malay community. This study aims to see the stigma of the Malay community towards people with mental disorders. Methodology: This research is descriptive research. The sample in this study was the Malay community with a total of 280 people and recruited by purposive sampling method. The data collection method uses a community attitude towards the mental illness (CAMI III) questionnaire which is conducted online. Results: This study shows that the majority of respondents are 17-25 years old (27.9%), with the highest gender being male (52.1%), and the last education is SMA/equivalent (48.9%). The image of the community's stigma against ODGJ is that the Malay community is pro against 3 dimensions, namely authoritarianism (55%), virtue (56.1%), and social restrictions (50.7%), while contra with 1 dimension, namely the ideology of the mental health community (52 ,1%). Conclution: The results of this study indicate that the Malay community is pro against 3 dimensions and contra against 1 dimension, namely community ideology. The researcher hopes that this research can be useful for the Malay community as an evaluation of the ideological dimensions of the mental health community.